Application of template metaprogramming technologies to improve the efficiency of parallel arrays - Jakušev, Alexander (Mathematical Modelling and Analysis, 2007)
Parallel array library ParSol is an easy way to parallelize data parallel algorithms implemented in C/C++. However, in order to use all the features provided by C++ and OOP in real life applications, the efficiency of C++ code that uses ParSol library must be similar to the one of C code. Template metaprogramming is one of the ways to achieve this goal. This paper describes the details of application of this technology to parallel arrays, and presents the efficiency tests.First Published Online: 14 Oct 2010